Moiré collapse and Luttinger liquids in twisted anisotropic homobilayers - Duarte J. P. de Sousa; Seungjun Lee; Francisco Guinea; Tony Low (Proceedings of the National Academy of Sciences, 2026)
We introduce twisted anisotropic homobilayers as a distinct class of moiré systems, characterized by a distinctive “magic angle,” θ M , where the moiré unit cell collapses. Unlike conventional studies of moiré materials, which primarily focus on small lattice misalignments, we demonstrate that this moiré collapse occurs at large twist angles in generic twisted anisotropic homobilayers. The collapse angle, θ M , is likely to give rise quasi-crystal behavior as well as to the formation of strongly correlated states, that arise not from flat bands, but from the presence of ultra-anisotropic electronic states, where non-Fermi liquid phases can be stabilized. In this work, we develop a continuum model for electrons based on extensive ab initio calculations for twisted bilayer black phosphorus, enabling a detailed study of the emerging moiré collapse features in this prototypical system. We show that the (temperature) stability criterion for the emergence of (sliding) Luttinger liquids is generally met as the twist angle approaches θ M . Furthermore, we explicitly formulate the collapsed single-particle one-dimensional (1D) continuum Hamiltonian and provide the fully interacting, Hamiltonian applicable at low doping levels. Our analysis reveals a rich landscape of multichannel Luttinger liquids, potentially enhanced by valley degrees of freedom at large twist angles.